(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Financial crime in India is the focus of this research. It provides an overview of the issuescurrently confronting the financial sector, as well as potential solutions. Cybercriminals often aim theirattacks at financial institutions. Gordon Snow, assistant director of the Cyber Division of the FederalBureau of Investigation, expects cyber assaults on financial institutions to increase in frequency andsophistication. The rise of e-commerce presents several new entry points for cybercriminals.